The subversive feminine : sexual oppression and sexual identity in Doris Lessing's The Golden Notebook. - Lalbakhsh, Pedram; Wan Yahya, Wan Roselezam (Canadian Academy of Oriental and Occidental Culture, 2011)
Doris Lessing’s The Golden Notebook adopts a complex profile to present its characters’ complex lives. However, of all existing novel’s themes it is women’s oppression and subjugation that come under scrutiny here. The world this novel pictures is a patriarchal capitalist world highly unfavorable to women, and the society it portrays is marked by male-dominance and genderbased discrimination; a society in which – no matter how capable women are – their identity is defined by men and male-defined relations. Accordingly, this paper is looking at this novel from a socialist feminist point of view to identify the facets of sexual oppression and to show how the female characters resist, fight back and rely on their self-defined identity to subvert the oppressive structure they are living in. Based on the findings of this paper we argue that in the novel’s world sexuality, motherhood and mothering are outstanding facets of oppression through which women are overwhelmingly oppressed and exploited by the male-dominated society that discriminates against women as a secondary inferior class. To our understanding, while female characters of the novel have to deal with a lot of pressure imposed by society’s institutions (family and family-like circles) they are capable enough to shrewdly rely on their power and self-defined identity to fight back and subvert the patriarchal capitalist systems that intrude women’s lives in a variety of ways. As we conclude Lessing confirms socialist feminism’s argument that mothering and motherhood are facets of women’s oppression, but she also believes that these two aspects of feminine life can be a part of feminine power to subvert the oppressive systems that are designed to define and enfeeble women’s genuine identity.